The Effectiveness of Monetary and Fiscal Policy in Serbia - Rakić, Biljana; Rađenović, Tamara (Industrija, 2013)
The effectiveness of fiscal and monetary policy has been the center of debate between Keynesians and the monetarists for a long time. However, the results from numerous empirical studies are inconclusive, suggesting that none of the policies can be thought of as superior to the other and their relative effectiveness in any economy depends on the prevailing economic and political conditions at any point in time. In order to determine the influence of fiscal and monetary policy on the economic activity in Serbia, we employed unit root and cointegration tests, as well as the regression analysis on the series of quarterly data for the period 2003-2012. The obtained results show that monetary policy is more effective in stimulating economic growth comparing to fiscal policy. Hence, the overall conclusion is that government should pay more attention to the fiscal policy to improve its efficiency in the future.